AI and Big Data in Advancing Mathematical Literacy Cybersecurity’s Moderating Role - Sumliyah; Wardono; Mariani, Scolastika; Budi Waluya, Stevanus; Pujiastuti, Emi; Ikhsan, Ramiro Santiago (Pandawan Sejahtera Indonesia, 2025)
In today’s rapidly evolving digital landscape, mathematical literacy has emerged as a crucial competency for students navigating data-intensive environments. The integration of Artificial Intelligence (AI) and Big Data in education holds transformative potential to enhance personalized learning and support data-driven teaching strategies, yet it also raises critical concerns around Cybersecurity, particularly in safeguarding student data and ensuring trust in digital platforms. This study aims to analyze the effects of AI and Big Data on mathematical literacy, while examining the moderating role of Cybersecurity. Using a quantitative research approach, data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. The results indicate that both AI and Big Data have significant positive effects on students’ mathematical literacy, with Big Data exerting the strongest influence through its ability to provide deep insights into student performance. AI also contributes effectively by enabling real-time feedback, adaptive learning, and personalized instruction. Although Cybersecurity demonstrated a weaker direct effect on mathematical literacy, it remains an essential enabler of a secure digital learning environment, fostering user trust and system integrity. This research highlights the importance of aligning educational technology implementation with strong digital safeguards to maximize learning outcomes. The findings offer managerial implications for educational institutions to invest in intelligent learning platforms supported by robust cybersecurity protocols. Ultimately, the study reinforces the relevance of SDG 4: Quality Education, by promoting inclusive, safe, and tech-enhanced learning ecosystems suited for the demands of 21st-century education.